MODEL PEMBELAJARAN PESANTREN KILAT DALAM MENANAMKAN NILAI-NILAI MORALITAS PADA SISWA SEKOLAH MENENGAH PERTAMA DI SALATIGA - Ari Setiawan (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
Students’ morality are changing over time in corresponding to the globalization era. This condition sometimes happens in the junior high school students. The Student fight to others shows the degradation of morality. Finding the solution by organizing Pesantren Kilat to respond morals degradation will be the crucial parts. This program may help teacher to turn their students on good morality. The problem of the research will be focused on the models of teaching in order to supply vision and mission of student moralities values in the form of Pesantren Kilat. An interview and observation was carried out in order to give theclues and detail information on the teaching models in Pesantren Kilat. The finding shows that behavioral technique through giving a good example has provided a significant changing on the students’ moral behavior. Even that there are several students point out that this program is only as part of Ramadhan activities, but at least it gives awareness on the students’ moral behavior.